The distribution and some ecological characteristics of Fokienia hodginsii (Dunn) A. Henry et H. H. Thomas and Cunninghamia konishii Hayata in Pu Huong Nature Reserve, Nghe An province - Thanh Nga, Nguyen Thi; Hieu, Nguyen Van; Dung, Nguyen Anh; Sim, Ma A; Thai, Tran Huy (Academia Journal of Biology, 2017)
Fokienia hodginsii (Dunn) Henry et Thomas and Cunninghamia konishii Hayata in Pu Huong Nature Reserve, Nghe An Province are localized in some mountainous areas bordered by 4 communes: Quang Phong (Que Phong District), Chau Hoan and Dien Lam (Quy Chau District) and Nga My (Tuong Duong District). Fokienia hodginsii is scatterly distributed or clusters in groups of 3-5 individuals, creating population from 50 to 150 trees, on grey feralit soil developed from acid magma and grey feralit soil developed from clay rock. It grows near the top of the mountains or on the mountains’ tops, at elevation range from 1,120 m to 1,385 m above sea level (a.s.l.), and has an average population density of 29.6 trees/ha. Cunninghamia konishii grows in a clusters of 3-7 individuals or creating subpopulation from 15 to 25 trees. It grows gradually up, from the ravine to the mountainside, at elevation from 1,060 m to 1,275 m a.s.l., on grey feralit soil developing from clay rock, and it has an average population density of 22.4 trees/ha. F. hodginsii populations have been found in many different exposures, Northeast, Northwest and Southwest, whereas Cunninghamia konishii subpopulations only distribute in two exposures, Northeast and Southwest. F. hodginsii and C. konishii are found in broadleaf forests and subtropical coniferous forests. They are usually mixed with species of families like Lauraceae, Clusiaceae, Elaeocarpaceae, Fagaceae, Theaceae, etc.   Citation: Nguyen Thi Thanh Nga, Nguyen Van Hieu, Ma A Sim, Nguyen Anh Dung, Tran Huy Thai, 2017. The distribution and some ecological characteristics of Fokienia hodginsii (Dunn) A. Henry et H. H. Thomas and Cunninghamia konishii Hayata in Pu Huong Nature Reserve, Nghe An Province. Tap chi Sinh hoc, 39(1): 122-128. DOI: 10.15625/0866-7160/v39n1.8849 *Corresponding author: nga17tv@gmail.com Received 10 November 2016, accepted 20 March 2017